SRSF2 mutations drive oncogenesis by activating a global program of aberrant alternative splicing in hematopoietic cells - Liang, Yang; Tebaldi, Toma; Rejeski, Kai; Joshi, Poorval; Stefani, Giovanni; Taylor, Ashley; Song, Yuanbin; Vasic, Radovan; Maziarz, Jamie; Balasubramanian, Kunthavai; Ardasheva, Anastasia; Ding, Alicia; et al. (Leukemia, 2018)
Recurrent mutations in the splicing factor SRSF2 are associated with poor clinical outcomes in myelodysplastic syndromes (MDS). Their high frequency suggests these mutations drive oncogenesis, yet the molecular explanation for this process is unclear. SRSF2 mutations could directly affect pre-mRNA splicing of a vital gene product; alternatively, a whole network of gene products could be affected. Here we determine how SRSF2 mutations globally affect RNA binding and splicing in vivo using HITS-CLIP. Remarkably, the majority of differential binding events do not translate into alternative splicing of exons with SRSF2 P95H binding sites. Alternative splice alterations appear to be dominated by indirect effects. Importantly, SRSF2 P95H targets are enriched in RNA processing and splicing genes, including several members of the hnRNP and SR families of proteins, suggesting a “splicing-cascade” phenotype wherein mutation of a single splicing factor leads to widespread modifications in multiple RNA processing and splicing proteins. We show that splice alteration of HNRNPA2B1, a splicing factor differentially bound and spliced by SRSF2 P95H , impairs hematopoietic differentiation in vivo . Our data suggests a model whereby the recurrent mutations in splicing factors set off a cascade of gene regulatory events that together affect hematopoiesis and drive cancer.